Work With Words Expressing The Concept Of Conflict In Reading Lessons - Khusanova Gulrukhsor Tulkin kizi (Zien Journals, 2023)
This article describes the creation of a database of tasks and an electronic dictionary for the formation of concepts of conflict in the minds of elementary school students and its impact on pupils. It is planned to improve the teaching of the Uzbek language to elementary school pupils by creating modern, new-generation educational dictionaries and their electronic forms and a dictionary of terms by field
Keywords: Vocabulary; opposite word; electronic dictionary; dictionary units